Roadmap and strategy for overcoming infusion reactions to nanomedicines. Issue 12 (December 2018) - Szebeni, Janos; Simberg, Dmitri; González-Fernández, África; Barenholz, Yechezkel; Dobrovolskaia, Marina
Abstract Infusion reactions (IRs) are complex, immune-mediated side effects that mainly occur within minutes to hours of receiving a therapeutic dose of intravenously administered pharmaceutical products. These products are diverse and include both traditional pharmaceuticals (for example biological agents and small molecules) and new ones (for example nanotechnology-based products). Although IRs are not unique to nanomedicines, they represent a hurdle for the translation of nanotechnology-based drug products. This Perspective offers a big picture of the pharmaceutical field and examines current understanding of mechanisms responsible for IRs to nanomedicines. We outline outstanding questions, review currently available experimental evidence to provide some answers and highlight the gaps. We review advantages and limitations of the in vitro tests and animal models used for studying IRs to nanomedicines. Finally, we propose a roadmap to improve current understanding, and we recommend a strategy for overcoming the problem. This Perspective analyses the infusion reactions triggered by nanomedicine administration and proposes a strategy to improve their mechanistic understanding and to reduce their negative outcomes.